2009
DOI: 10.1186/gb-2009-10-1-r5
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of versatile high density microarrays for genome-wide analysis of Streptomyces coelicolor: characterization of the HspR regulon

Abstract: Development of high-density microarrays for global analysis of gene expression and transcription factor binding in Streptomyces coelicolor suggests a novel role for HspR in stress adaptation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 65 publications
2
42
0
Order By: Relevance
“…Therefore, the GlxR-binding sites located far from the coding region could not be detected by the microarray, as has been described by others (27,52). False negatives may also occur in ChIP-chip experiments due to sequestration of the transcription factor in nucleoprotein complexes, rendering them inaccessible to the specific test antibody used for the IP reaction (12,30). Of the binding sites not detected by ChIP-chip analyses in this study, 21 have been shown to bind to GlxR in EMSA (42,43).…”
Section: Vol 193 2011mentioning
confidence: 92%
See 1 more Smart Citation
“…Therefore, the GlxR-binding sites located far from the coding region could not be detected by the microarray, as has been described by others (27,52). False negatives may also occur in ChIP-chip experiments due to sequestration of the transcription factor in nucleoprotein complexes, rendering them inaccessible to the specific test antibody used for the IP reaction (12,30). Of the binding sites not detected by ChIP-chip analyses in this study, 21 have been shown to bind to GlxR in EMSA (42,43).…”
Section: Vol 193 2011mentioning
confidence: 92%
“…In addition, the cyaB mutant is able to grow on any carbon source much better than a glxR mutant (15,59), implying that GlxR may be physiologically functional even in the cyaB mutant background. Chromatin immunoprecipitation in conjunction with microarray (ChIP-chip) analysis has been used to identify in vivo target sites and physiological states of bacterial transcriptional regulators in recent years (12,17,27,30,31,52,60,66). The regions bound by the transcriptional regulator are enriched by ChIP, and the degrees of the enrichment reflect the ability of the regulator to bind to the regions in the cells under the conditions tested.…”
mentioning
confidence: 99%
“…Before use, the RNA samples were checked for integrity on an Agilent 2100 Bioanalyzer (Agilent Technologies), and lack of DNA was checked by reverse transcription-PCR (RT-PCR) without reverse transcriptase. cDNA preparation, labeling, and hybridization was performed as previously described (41,42). For the microarray analysis, 4ϫ44K whole-genome Streptomyces arrays (Agilent Technologies) were used (42).…”
Section: Methodsmentioning
confidence: 99%
“…cDNA preparation, labeling, and hybridization was performed as previously described (41,42). For the microarray analysis, 4ϫ44K whole-genome Streptomyces arrays (Agilent Technologies) were used (42). The filtered data sets were analyzed using rank product analysis (43) via the Rank-Prod package in R (version 2.5.0) (44).…”
Section: Methodsmentioning
confidence: 99%
“…The feature extraction output files were imported into R (software programming language) (version 2.5.0; http://www.R-project.org) and normalized using the LIMMA package (18); global median within-array normalization followed by "scale" across-array normalization was applied to the log 2 [cDNA/gDNA] ratios of the expression arrays. Flagging of poor-quality spots was performed (19), and probes were filtered out of the data set if they did not yield a good-quality spot across gene expression data sets. Probes targeting the coding regions of a gene were averaged such that each annotated protein-encoding gene of S. coelicolor was represented by a single value.…”
mentioning
confidence: 99%